Comparison of Berkovich and spherical tip indentation for determining the Young’s modulus of polymer thin films encapsulated by a dielectric - Marina Melo de Lima; Vincent Mandrillon; Jennifer Hay; Laurent-Luc Chapelon; Christophe Poulain; Olivier Lebaigue (Acta Polytechnica CTU Proceedings)
Pixel integrated micro-lenses for CMOS image sensors consist of a stack of polymer acrylate resin films encapsulated by a dielectric layer. Due to the mismatch of thermomechanical properties, adhesive or cohesive fractures can occur. This can lead to reliability issues requiring the knowledge of the polymer thermomechanical properties. Nanoindentation is a standard method for determining Young’s modulus of thin films. However, when performing temperature-dependent nanoindentation studies directly on the polymer film, contamination of the tip can occur near or above the glass transition temperature leading to estimation errors. Therefore, the polymer films must be measured including a protective layer, and a multilayer model is used to extract the polymer’s Young’s modulus. Finite-element simulations of Berkovich and spherical indentations on the complete stack were performed, enabling the identification of a contact radius range within which the relative error resulting from using the multilayer model is less than 10 %. Consequently, room temperature and temperature-dependent tests of the complete stack were performed, enabling the determination of the polymer’s Young’s modulus as a function of temperature without tip contamination.